Numerical study of wave run-up on a fixed surfacepiercing cylinder in non-breaking waves - Mohseni, Mohammad (2018)
In wave-structure interaction, wave run-up is an important phenomenon that needs to be considered in the design of offshore structures. A thorough understanding of the physics of the nonlinear flow phenomena is necessary for the better insight into the runup phenomenon. The present work, primarily, is focused on the hydrodynamic simulation of wave run-up and mainly seeks to evaluate the importance of highfrequency wave scattering types identified by Swan-et al. [2005] and lateral progressive edge waves on nonlinear wave amplification around a single fixed cylinder. The physics of the problem involves the interaction of single surface piercing cylinder with surface gravity incident waves which are propagating over a flat bed in an unbounded domain in deep water. The analysis is performed numerically using CFD based Navier-Stokes equations and Potential-flow theory. The numerical results are compared with experimental data provided by ITTC (OEC),[2013]. Taking into account the numerical simulation of the physical mechanism of wave scattering around the cylinder, the first part of the thesis deals with the investigation of the importance of the aforementioned high-frequency wave scattering and also lateral edge waves on nonlinear wave field and also inline wave force over a range of wave steepnesses and wavelengths. Then the Influence of potential flow, viscous and turbulence effects on wave run-up is explored. Afterward, in the second part of the thesis, the effects of the change in cylinder submerged geometry and finally, change in cross-section on the wave field around the cylinder is studied.